2017
DOI: 10.1371/journal.pbio.2002711
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine externalization, “necroptotic bodies” release, and phagocytosis during necroptosis

Abstract: Necroptosis is a regulated, nonapoptotic form of cell death initiated by receptor-interacting protein kinase-3 (RIPK3) and mixed lineage kinase domain-like (MLKL) proteins. It is considered to be a form of regulated necrosis, and, by lacking the “find me” and “eat me” signals that are a feature of apoptosis, necroptosis is considered to be inflammatory. One such “eat me” signal observed during apoptosis is the exposure of phosphatidylserine (PS) on the outer plasma membrane. Here, we demonstrate that necroptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
178
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(201 citation statements)
references
References 42 publications
16
178
0
Order By: Relevance
“…Apoptosis, as well as the regulated non-apoptotic forms of cell death (necroptosis and pyroptosis), can influence hematopoiesis following infection or in the setting of bone- marrow transplantation 13 . The demonstration that annexin V staining of hematopoietic stem and progenitor cells is diminished in the absence of OPN following transplantation or infection might also be consistent with descriptions of annexin V staining of cells undergoing non-apoptotic cell death 14,15 . iOPN and sOPN might also regulate the expression of regulators of these non-apoptotic forms of cell death, in addition to that of genes encoding apoptotic molecules such as survivin and Bcl-x L .…”
supporting
confidence: 83%
“…Apoptosis, as well as the regulated non-apoptotic forms of cell death (necroptosis and pyroptosis), can influence hematopoiesis following infection or in the setting of bone- marrow transplantation 13 . The demonstration that annexin V staining of hematopoietic stem and progenitor cells is diminished in the absence of OPN following transplantation or infection might also be consistent with descriptions of annexin V staining of cells undergoing non-apoptotic cell death 14,15 . iOPN and sOPN might also regulate the expression of regulators of these non-apoptotic forms of cell death, in addition to that of genes encoding apoptotic molecules such as survivin and Bcl-x L .…”
supporting
confidence: 83%
“…Furthermore, molecules released by neutrophils such as neutrophil gelatinase‐associated lipocalin can enhance efferocytosis by increasing the expression of the phosphatidylserine receptor MER proto‐oncogene, tyrosine kinase on macrophages . More recently, necroptosis, a regulated, nonapoptotic form of necrotic cell death has been shown to cause expression of “eat me signals” by neutrophils, thus enhancing efferocytosis by macrophages and improving the outcome after myocardial injury …”
Section: Neutrophil–macrophage Cooperation During Tissue Repairmentioning
confidence: 99%
“…Similar to apoptosis, necroptosis can likewise be reversed . Although necrosis used to be considered as an ‘accidental’ cell death beyond any regulation, studies have revealed a comprehensive signaling pathway resulting in the form of necrosis called necroptosis .…”
Section: Necroptosismentioning
confidence: 99%
“…After MLKL phosphorylation, necroptotic cells undergo a series of biological events, including Ca 2+ influx, phosphatidylserine (PS) externalization, and the final compromise of PM integrity. If RIPK3 or MLKL is inactivated at the PS exposure stage, some of the necroptotic cells can fully recover . These dying cells can reattach to the culture surface, regain normal morphology, re‐establish PS asymmetry, lower intracellular Ca 2+ to the resting level, and inactivate or dephosphorylate MLKL.…”
Section: Necroptosismentioning
confidence: 99%
See 1 more Smart Citation